The effect of heat treatment and chromium addition on γ-titanium aluminide resistance to hydrogen attack - Suardi, Khairmen (2005)
The intermetallic alloys of γ-titanium aluminide are emerging as one of the most attractive alternative structural and machinery part materials for high and low temperature applications. One critical area of application is in hydrogen storage tank in chemical, oil and gas industries or in combustion engine when entail the use of hydrogen as a fuel. It has been widely reported by researchers that these materials exhibit environmental embrittlement in the presence of hydrogen, hence the diffusivity of hydrogen and the effect of hydrogen to the mechanical properties of γ-titanium aluminide is significant and technologically important. Therefore, in the present research, an investigation had been carried out to determine what causes the hydrogen attack and dealuminification. Control microstructure and phases through heat treatment by heating to 12000C for 30 minutes and cooled in three different ways (i.e. waterquenched, air-cooled and furnace-cooled), and addition of a third alloying element namely chromium become the focus of this research. Samples were subjected to corrosion attack under cathodically charged with galvanostatic mode for 6, 24 and 48 hours. Hydrogen diffusion coefficient (D) was calculated based on Fick’s second Law and these results were compared with that obtained from micro-Vickers hardness profiling data. The corroded and uncorroded samples were analyzed by using x-ray diffraction (XRD), scanning electron microscopy (SEM) and secondary ion mass spectroscopy (SIMS). It was found that α2-Ti3Al or lamellae phases are more prone to hydrogen attack than γ-TiAl phases but γ-TiAl is more susceptible to dealuminification. Slowly cooled (furnace-cooled) Ti-Al exhibited the least hydrogen attack due to its low hydrogen diffusion coefficient. However the effect of heat treatment on dealuminification is insignificant. When γ-titanium aluminide were alloyed with chromium, their resistance towards hydrogen attack and dealuminification increased.